2006
DOI: 10.1366/000370206778998978
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fourier Transform Raman Spectroscopy for Prediction of Bitterness of Peptides

Abstract: The potential application of Fourier transform (FT) Raman spectroscopy to predict the bitterness of peptides was investigated. FT-Raman spectra were measured for the amino acid Phe and 9 synthetic di-, tri-, and tetra peptides composed of Phe, Gly, and Pro. Partial least squares regression (PLS)-1 analysis was applied to correlate the FT-Raman spectra with bitterness intensity values (R(caf) and log 1/T) reported in the literature. Using full cross-validation, Model 1 based on the single spectral data set for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…It may suggest that the presence of an additional amino acid ("Aa") in a tripeptide sequence could intensify its bitterness, which can be explained by the use of chemometric methods like PCA. For example, peptides GGF and GGY were found as bitter like GG-Aa type peptides due to the presence of bulky and high molecular weight residues [34], which was also observed in our PCA results (see Table 3). …”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…It may suggest that the presence of an additional amino acid ("Aa") in a tripeptide sequence could intensify its bitterness, which can be explained by the use of chemometric methods like PCA. For example, peptides GGF and GGY were found as bitter like GG-Aa type peptides due to the presence of bulky and high molecular weight residues [34], which was also observed in our PCA results (see Table 3). …”
Section: Resultssupporting
confidence: 82%
“…Relatively high molecular weight of a given amino acid resulted also from the increasing number of carbon and hydrogen atoms, which was also revealed in the obtained PCs. Kim and Li-Chan [34] reported that high molecular weight of amino acids had the impact on peptides' bitterness, which also influenced their hydrophobicity. Peptides composed of F and/or Y (with a relatively high molecular weight) were reported to be bitter [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the presence of bulky C‐terminal amino acid in a peptide sequence affected its bitterness. When looking at the sequences of dipeptides analyzed, we reported that they were composed mostly of amino acids with branched and bulky side chains (both N‐ and C‐terminal) like, for example, L, I, V, G, and F. The presence of branched side chains or ring affected the molecular weight of a whole peptide (Kim & Li‐Chan, ). The analysis of di‐ and tripeptide data sets indicated that most of di‐ and tripeptides possessed N‐ or C‐terminal residues with a cyclic and/or aromatic ring like P, F, and Y.…”
Section: Resultsmentioning
confidence: 99%